Second Temple Pseudepigraphy: A Cross-cultural Comparison of Apocalyptic Texts and Related Jewish Literature - Dobroruka, Vicente (Ekstasis, 2013)
Main description: At this point of the scholarly debate on the nature of Second Temple pseudepigraphy, one may ask why another look at the problem is needed. This book is not the definitive answer to that problem but it proposes different paths - or better still, a two-fold path: on one hand to understand Second Temple pseudepigraphy as a mystical experience and on the other, for lack of a suitable ancient example, to compare it to modern-day automatic writing.